2018
DOI: 10.1111/jcmm.13471
|View full text |Cite
|
Sign up to set email alerts
|

ACE2‐EPC‐EXs protect ageing ECs against hypoxia/reoxygenation‐induced injury through the miR‐18a/Nox2/ROS pathway

Abstract: Oxidative stress is one of the mechanisms of ageing‐associated vascular dysfunction. Angiotensin‐converting enzyme 2 (ACE2) and microRNA (miR)‐18a have shown to be down‐regulated in ageing cells. Our previous study has shown that ACE2‐primed endothelial progenitor cells (ACE2‐EPCs) have protective effects on endothelial cells (ECs), which might be due to their released exosomes (EXs). Here, we aimed to investigate whether ACE2‐EPC‐EXs could attenuate hypoxia/reoxygenation (H/R)‐induced injury in ageing ECs thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 37 publications
4
73
0
Order By: Relevance
“…Arterial and venous endothelial cells express angiotensin-converting enzyme 2 (ACE2), which is now suggested to protect against ischemia-induced cerebral injuries. When exosomes of endothelial progenitor cells are transfected with lentivirus containing human ACE2 cDNA (ACE2-EPC-EXs), a protective effect on hypoxia/reoxygenation (H/R)-induced injury in cultured aging brain endothelial cells emerges [ 49 ]. However, only a partial protection is observed with ACE2-EPC-EXs anti-miR-18a , suggestive of miR-18a involvement.…”
Section: Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial and venous endothelial cells express angiotensin-converting enzyme 2 (ACE2), which is now suggested to protect against ischemia-induced cerebral injuries. When exosomes of endothelial progenitor cells are transfected with lentivirus containing human ACE2 cDNA (ACE2-EPC-EXs), a protective effect on hypoxia/reoxygenation (H/R)-induced injury in cultured aging brain endothelial cells emerges [ 49 ]. However, only a partial protection is observed with ACE2-EPC-EXs anti-miR-18a , suggestive of miR-18a involvement.…”
Section: Endotheliummentioning
confidence: 99%
“…However, only a partial protection is observed with ACE2-EPC-EXs anti-miR-18a , suggestive of miR-18a involvement. Subsequent analysis revealed that the observed protection is mediated through anti-apoptotic and anti-oxidative effects via the miR-18a/Nox2/ROS pathway [ 49 ]. In a more recent study, ACE2-EPC-exosomes were shown to protect cerebral microvascular endothelial cells with Ang II-induced injury against apoptosis, ROS generation, mitochondrion fragmentation, and reduced tube formation and migration abilities.…”
Section: Endotheliummentioning
confidence: 99%
“…Cellular senescence is defined as the stable cell cycle arrest elicited in response to a variety of stressors (37). The accumulation of oxidative stress in cardiomyocytes has been reported to cause senescence and reduce cardiac function (18). Radiation-associated oxidative stress and telomere loss have all been linked to the induction of the senescent phenotype through replication stress-induced DNA damage (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is an important inducer of cardiomyocyte senescence (18), with radiation being a major cause of reactive oxygen species (ROS) production (19). Upregulation of antioxidant proteins, such as endothelial nitric oxide synthase (eNOS) and catalase, has been demonstrated to protect against oxidative stress-mediated senescence (20).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that miR-18a expression was decreased in aging ECs and miR-18a protects ECs from hypoxia/reoxygenation-induced injury by downregulating the Nox2/ROS pathway [74]. In addition, some components of the miR-17-92 cluster (miR-18a, miR-17-5p, and miR-20a) may participate in the control of angiogenic phenotypes such as the proliferation, survival, [75]. Further, miR-214, which is highly expressed in ECs, is enriched in EC-derived exosomes; senescent cells with reduced miR-214 levels can be rescued by absorbing exosomal miR-214 produced by neighboring cells.…”
Section: Mirnas and Lncrnas In Vascular Agingmentioning
confidence: 99%